2011
DOI: 10.1007/s10517-011-1220-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Peculiarities of Mast Cells in Undifferentiated Connective Tissue Dysplasia

Abstract: We performed an immunomorphological study of mast cells from undamaged skin in women with phenotypical evidence of undifferentiated connective tissue dysplasia syndrome, patients of cosmetological clinics. It was found that the numerical density of mast cells containing chymase granules in this condition 1.7-fold surpassed the corresponding parameter in patients without signs of connective tissue dysplasia syndrome, which probably was a result of compensatory and adaptive reaction aimed at activation of the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…Moreover, evidence in this context has suggested that women workers may be concentrated into fewer and lower-paid occupations per OSC classification than men [79]. Second, the OSC may not accurately identify the SEP of individuals outside of the market labor force, such as the unemployed, retired adults, children, and individuals employed in informal sectors, such as homemakers [81]. Although head-of-household OSC measures may be used as proxies for measuring SEP among individuals who fall into the above classifications, these proxies do not account for differences in family structure and/or dependency in relation to the head-of-household.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, evidence in this context has suggested that women workers may be concentrated into fewer and lower-paid occupations per OSC classification than men [79]. Second, the OSC may not accurately identify the SEP of individuals outside of the market labor force, such as the unemployed, retired adults, children, and individuals employed in informal sectors, such as homemakers [81]. Although head-of-household OSC measures may be used as proxies for measuring SEP among individuals who fall into the above classifications, these proxies do not account for differences in family structure and/or dependency in relation to the head-of-household.…”
Section: Discussionmentioning
confidence: 99%
“…Of those receiving 10 mg or more of gluten daily, one had symptomatic relapse and several showed worsening CD on histological examination. 7 Yet the study concluded that, for patients with CD, the daily dietary intake of gluten should be <50 mg. 7 Note 10 mg in 500 g of food represents 20 ppm; 10 mg gluten is ingested in 1/250th of a slice of bread containing 2.5 g gluten. 4 Does any label tell us how much gluten is contained within said package?…”
Section: Mast Cells Are Obviously Not a Glial Subtype But These Perimentioning
confidence: 99%
“…6 These ASICs are a new migraine pharmacological target. 7 I presume it's only a matter of time before direct linkage is made between nervous tissue, immune cells, and pain, if I haven't already misrecognized it. Background and purpose: Migraine and irritable bowel syndrome (IBS) share many similarities characterized by their epidemiology, periodic pain, lack of definable organic causes, trigger factors, comorbidities, and proposed pathophysiology.…”
Section: Mast Cells Are Obviously Not a Glial Subtype But These Perimentioning
confidence: 99%
See 2 more Smart Citations